What Kind of Relationship Do Arab Historians Have With Ottoman Sources? - stiti, Mustafa (The Algerian Historical Journal, 2026)
This paper looks into the topic of Ottoman sources and shows how rich and diverse they are. It also discusses their importance to Arab historians and others, in their research. It specifically focuses on the position of Ottoman sources in writing the history of Arab countries from different aspects: political, economic, social and cultural. The work equally explores the position of Ottoman studies in the West, Turkey and Arab countries. The researcher concludes that the Ottoman studies in Arab countries are still beset with backwardness and rigidity. This is due to a number of historical, political, ideological and linguistic reasons. It is worthwhile noting that the events that followed the World War I, the fall of the Ottoman Caliphate, and disintegration of the Ottoman Empire into statelets have left a deep impact in the minds of both Turkish and Arab people and caused a major political and intellectual schism, the effect of which is alive till this day in the Turkish and Arab mentality. The paper opines that in spite of efforts being made to get out of this unfortunate situation; Arab studies in Turkish and Ottoman arenas are still stagnant. The paper finally suggests steps that aim at stimulating historical research in Ottoman sources and establishing academic relations between Arab universities and research centers, and their Turkish counterparts.Enter your abstract here (an abstract is a brief, comprehensive summary of the contents of the article). Enter your abstract here (an abstract is a brief, comprehensive summary of the contents of the article).